Distributed processor allocation in large PC clusters - De Rose, C.A.F.; Heiss, H.-U.; Navaux, P.A.O. (High Performance Distributed Computing (HPDC-9, 2000): 9th IEEE International Symposium, 2000)
Current processor allocation techniques for highly parallel systems are based on centralized front-end based algorithms. As a result, the applied strategies are restricted to static allocation, low parallelism and weak fault tolerance. To lift these restrictions, we are investigating a distributed approach to the processor allocation problem in large distributed memory machines. A contiguous and a noncontiguous version of a distributed dynamic processor allocation strategy are proposed and studied. Simulations compare the performance of the proposed strategies with that of well-known centralized algorithms. We also present the results of experiments on a Simens hpcline Primergy Server with 96 nodes that show distributed allocation is feasible with current technologies.